Epilepsy - Miller, John W. (John William), 1951-; Goodkin, Howard P. (Neurology in practice (Series), 2013)
Epilepsy is a complicated neurological condition with variable manifestations, numerous etiologies, and a diverse range of treatments. It is a chronic disease that, in many cases, can be controlled. However, treatment requires accurate clinical evaluation to allow intelligent treatment choices. Epilepsy has been designed to help clinicians develop these evaluation skills. Expert neurologists have distilled the evidence and combined their experience.